PTH-131 Multi-centre comparative effectiveness of vedolizumab and ustekinumab as induction therapy in anti-TNF refractory Crohn's disease. (June 2019) - ,; Razanskaite, Violeta; Michail, Stephanie; Morgan, James; Davies, Michael; Storey, Daneil; Watters, Christopher; Penman, Douglas; Swaminathan, Mira; Sabine, Joseph; Chapman, Adam; Reilly, Ian; et al.
Abstract : Introduction: Anti-tumour necrosis factor (TNF) agents are effective in Crohn's disease (CD), but up to 30% of patients fail to respond or develop intolerance and require alternative biological therapy. Both vedolizumab and ustekinumab are licensed to treat anti-TNF refractory CD patients. Clinical trials of vedolizumab and ustekinumab in anti-TNF refractory patients seem to suggest comparable efficacy, but no real life data exist to enable clinicians to guide decision-making. We conducted a multi-centre retrospective cohort study to assess the comparative effectiveness of vedolizumab and ustekinumab in treating anti-TNF refractory CD. Methods: CD patients who were commenced on vedolizumab or ustekinumab following exposure to anti-TNF therapy were included. Disease activity was monitored serially by calculation of Harvey-Bradshaw index (HBI) for up to 4 months. Faecal calprotectin (FC) at baseline and subsequent visits were recorded if available. Clinical response was defined as decrease in HBI ≥3 and remission by HBI <5. We compared the effectiveness of ustekinumab and vedolizumab. Results: After exclusion of patients without evaluable data, 51 patients commencing vedolizumab and 25 commencing ustekinumab therapy were included. Baseline characteristics (age, disease location, behaviour, smoking status and baseline FC) were comparable in both cohorts. Clinical response, remission and steroid-free remission rates were comparable between vedolizumab and ustekinumab at 2 and 4 months (see table 1 ). There was a significant reduction in HBI for vedolizumab at 2 months (1.8, 95% CI 0.50 to 3.13, p = 0.008) and ustekinumab at 4 months (3.4, 95% CI 1.84 to 4.96, p = 0.0001). Conclusions: In a multi-centre cohort of anti-TNF refractory CD patients, vedolizumab and ustekinumab appear equally effective in the short-term. Our observations warrant longer-term follow up and further validation in independent cohorts.